(3efJNH ef ebGdI aj GdfaSs - (3bSWG Hf dhbG GdHYdHcj,J (B300 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI bGd EaCeG GdfaS aEf hUagG Ydi MbjbJgG UYH LOGU hGdOdjd Ydi Pdc GNJdGa CLdI GdMceGA cCadGWf hCQSWGWGdjS hNQhSjS hZjQge ajgG s
(3BNQgG (B:s
(3hdjS CMSf GdPhb dCfg dG jZJPj ef TF hSfNHQ cja JYde GdfaS GdCTjGA hcja JYQa aYd GdUhQI hcja JMSf GdMhGS eMShSGJgG HMLL eVjFI s
(3Vef eLehY , JQJjHgG (B: 21s
(3UfYI Edi YjSj Hf aQNGfTGgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B131s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs